Cognitive Ai Analysis For Prediction Of Changes In Public Behavior In Public Relations Management In Schools - Aminullah Aminullah; Moh Mohlas; Muhammad Durrin Ni’am; Najiburrahman Najiburrahman; Hasan Baharun (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
Abstract: This study aims to examine the use of Cognitive AI in predicting changes in public behavior in the background of public relations management in schools, especially in improving the effectiveness of data-based communication and decision-making strategies. Through this approach, it is hoped that schools will be able to master the response patterns of school residents more accurately, in routine situations when communication crises occur. The research method used is qualitative in the form of a case study, involving in-depth interviews, directed observations, and document analysis to thoroughly explore the process of implementing Cognitive AI and its impact on school communication management patterns. The results indicate that the use of Cognitive AI can recognize changing trends in public opinion, improve the accuracy of PR messages, and help schools design more responsive and personalized communication strategies. After all, the application of technology also strengthens the school's relationship with publications through a more productive and sustainable understanding of behavior. The implications of this study confirm that the integration of Cognitive AI not only improves the effectiveness of public relations management, but also becomes the basis for innovation in designing adaptive and sustainable educational communication.